High‐power mode‐hop‐free tunable DFB laser at 780 nm - Matthias Reggentin; Olaf Brox; Poojitha Sammeta; Pietro Della Casa; Christoph Stölmacker; Sten Wenzel; Jan‐Philipp Koester; Hans Wenzel; Andrea Knigge (Electronics Letters, 2024)
Abstract A distributed feedback laser with integrated quarter‐wave phase shift and more than 100 mW optical output power at an emission wavelength of 780 nm is presented. The laser provides mode‐hop‐free tuning over a wide range of injections currents and operating temperatures by design and can serve as an enabling component for more complex systems such as chips with additional monolithically integrated amplifiers, chip arrays and sources for hybrid integrated photonic circuits.